Commercially available carbohydrate drink with menthol fails to improve thermal perception or cycling exercise capacity in males. Issue 11 (2nd November 2022) - Podlogar, Tim; Bolčič, Tina; Cirnski, Simon; Verdel, Nina; Debevec, Tadej
ABSTRACT: The purpose of this double-blinded, crossover randomized and counterbalanced study was to compare the effects of ingesting a tepid commercially available carbohydrate–menthol-containing sports drink (menthol) and an isocaloric carbohydrate-containing sports drink (placebo) on thermal perception and cycling endurance capacity "in a simulated home virtual cycling environment". It was hypothesized that the addition of menthol would improve indicators of thermal perception and improve endurance exercise capacity. Twelve healthy, endurance-trained males (age 29 ± 5 years, height 181 ± 6 cm, body mass 79 ± 2 kg and V̇O2 max 57.3 ± 6.4 mL kg −1 min −1 ) completed two experimental trials on a stationary bicycle without external air flow. Each trial consisted of (1) cycling for 60 min at 90% of the first ventilatory threshold while receiving a fixed amount of menthol or placebo every 10 min followed immediately by (2) cycling until volitional exhaustion (TTE) at 105% of the intensity corresponding to the respiratory compensation point. TTE did not differ between both conditions (541 ± 177 and 566 ± 150 s for menthol and placebo; p > 0.05) and neither did ratings of perceived thermal comfort or thermal sensation ( p > 0.05). Also, the rectal temperature at the end of TTE was comparable between menthol and placebo trials (38.7 ± 0.2°C and 38.7 ± 0.3°C, respectively; p > 0.05). The present results demonstrate that the addition of menthol to commercially available sports drink does not improve thermal comfort or endurance exercise capacity during ∼65 min of intense virtual cycling. Highlights Ingestion of a commercially available carbohydrate–menthol beverage at high exercise intensity and without air flow does not improve endurance exercise capacity. When ingested with carbohydrates, it appears that a combination of carbohydrates and menthol does not improve thermal discomfort caused by intense exercise and a lack of air flow. A menthol concentration higher than 0.01% might be required to induce the reduction in thermal discomfort when ingested in combination with carbohydrates.